(untitled) (International Journal of Biology and Chemistry, 2024)
Assessment of the composition of peripheral blood cells and red bone marrow in preclinical studies is a key component of program for analysis of biologically active compounds obtained from the plant materials. Current study concerns effect of the complex extract from Rumex plants (R. confertus, R. tianschanicus, R. thyrsiflorus) on parameters of blood cells and bone marrow of laboratory animals. During the study, data were obtained on the effect of the extract on hematopoiesis when administered at 100 mg/kg of animal weight. The results obtained show that application of the extract is accompanied by a statistically significant increase in the number of neutrophil precursors, such as myeloblasts and band neutrophils (p≤0.05). According to our results the extract we obtained from Rumex plants does not cause inhibition of early bone marrow precursors and is safe and non-toxic.